PENGARUH JUMLAH UANG BEREDAR, INFLASI DAN NILAI TUKAR RUPIAH TERHADAP PENDAPATAN NASIONAL DI INDONESIA MENGGUNAKAN MODEL DINAMIS - Zakiah Zakiah; Umaruddin Usman (Jurnal Ekonomi Regional Unimal, 2019)
This study aims to determine the effect of the money supply, inflation and the rupiah exchange rate on national income in Indonesia. This study uses time series data from 1996-2017 obtained from www.bi.go.id, and www.bps.go.id. The tool used to analyze data is the Vector Autoregression Model (VAR) with the Impulse Respo Function (IRF). Based on research that uses the results of the VAR analysis model which shows that there is a unidirectional relationship between the variable money supply to national income and the unidirectional relationship between national income and the rupiah exchange rate. The results of the study with the analysis of the response response of the money supply took one year, the inflation variable took four years, and the exchange rate variable took three years to be stable after the shock caused by other variables in the study.